Arterial stiffness is associated with increased symptom burden in patients with atrial fibrillation - Kranert, Malte; Shchetynska-Marinova, Tetyana; Berghoff, Tim; Liebe, Volker; Doesch, Christina; Papavassiliu, Theano; Custodis, Florian; Akın, Ibrahim; Borggrefe, Martin; Hohneck, Anna (The Canadian journal of cardiology, 2020)
Background - Increased arterial stiffness (AS) has been described as a predictor of atrial fibrillation (AF). This study was performed to assess whether increased AS leads to a higher symptom burden in patients with AF. - Methods - One hundred sixty-two consecutive patients (104 male, 58 female) with diagnosed AF (paroxysmal or persistent) were enrolled. Symptoms most likely attributable to AF were quantified according to the Canadian Cardiovascular Society Severity of Atrial Fibrillation (SAF) scale. AS indices (aortic distensibility, cyclic circumferential strain, and aortic compliance) were characterized using transoesophageal echocardiography. - Results - The cohort was divided into asymptomatic to oligosymptomatic (SAF scale 0-1, n = 78 [48.1%]) and symptomatic (SAF scale ≥ 2, n = 84 [51.9%]) patients. Symptomatic patients tended to be younger (median, 75 [interquartile range (IQR) 67-80] vs 71 [65-79]; P = 0.047) and were more likely to be female (22 [28.2%] vs 36 [42.9%]; P = 0.052). Hypertension was more frequent in symptomatic patients. Aortic compliance indices each were reduced in symptomatic patients, most pronounced for aortic compliance (median, 0.05 [IQR 0.03-0.06] vs 0.04 [0.03-0.05] cm/mm Hg; P = 0.01) followed by cyclic circumferential strain (median, 0.09 [IQR 0.07-0.11] vs 0.07 [0.04-0.10]; P = 0.02) and aortic distensibility (10−3 mm Hg−1, median, 1.74 [IQR 1.34-2.24] vs 1.54 [1.12-2.08]; P = 0.03). Multivariable analysis revealed aortic compliance as an independent predictor for symptoms in patients with AF with an odds ratio of 2.6 (95% confidence interval, 1.2-3.4; P = 0.003). - Conclusions - AS contributes to a high symptom burden in patients with AF, emphasizing the prognostic role of AS in the early detection and prevention in patients with AF. - Résumé - Contexte - L'augmentation de la rigidité artérielle (RA) a été décrite comme un prédicteur de la fibrillation auriculaire (FA). Cette étude a été réalisée pour évaluer si l'augmentation de la RA entraîne une augmentation de la contrainte liée aux symptômes chez les patients atteints de FA. - Méthodes - Cent soixante-deux patients successifs (104 hommes, 58 femmes) pour lesquels une FA a été diagnostiquée (paroxystique ou persistante) ont été recrutés. Les symptômes les plus à même d’être attribués à la FA ont été quantifiés selon l'échelle de sévérité de la fibrillation auriculaire (SFA) de la Société canadienne de cardiologie. Les indices de RA (distension de l’aorte, contrainte circonférentielle cyclique et compliance aortique) ont été caractérisés à l'aide d'une échocardiographie transœsophagienne. - Résultats - La cohorte a été divisée entre patients asymptomatiques avec peu de symptômes (échelle SFA 0-1, n = 78 [48,1%]) et symptomatiques (échelle SFA ≥ 2, n = 84 [51,9%]). Les patients symptomatiques étaient généralement plus jeunes (médian, 75 [intervalle interquartile (IIQ) 67-80] contre 71 [65-79] ; P = 0,047) et étaient le plus souvent des femmes (22 [28,2 %] contre 36 [42,9 %] ; P = 0,052). L'hypertension était plus fréquente chez les patients symptomatiques. Les indices de compliance aortique étaient tous réduits chez les patients symptomatiques, de façon plus prononcée concernant la compliance aortique (médian, 0,05 [IIQ 0,03-0,06] contre 0,04 [0,03-0,05] cm/mm Hg; P = 0,01), suivie par la contrainte circonférentielle cyclique (médian, 0,09 [IIQ 0,07-0,11] contre 0.07 [0,04-0,10]; P = 0.02) et la distension aortique (10-3 mm Hg-1, médian, 1,74 [IIQ 1,34-2,24] contre 1,54 [1,12-2,08]; P = 0,03). L'analyse multivariable a révélé la compliance aortique comme prédicteur indépendant en ce qui concerne les symptômes chez les patients souffrant de FA avec un rapport de cotes de 2,6 (intervalle de confiance à 95 %, 1,2-3,4; P = 0,003). - Conclusions - La RA contribue à une charge symptomatique élevée chez les patients atteints de FA, ce qui souligne le rôle pronostique de la RA dans la détection précoce et la prévention chez les patients atteints de FA.